Seroprevalence of Brucellosis in Individuals Engaged in Animal Husbandry in Erzurum Region - Ahmet Yılmaz; Selahattin Çelebi; Sinan Yılmaz; Mahmut Ucar (Genel Tıp Dergisi)
Objective: Brucellosis is one of the most common zoonotic diseases in our country and the world. This study investigated the seroprevalence of brucellosis in individuals who were engaged in animal husbandry in Erzurum region, were over 18 years of age, or did not have any clinical complaints of brucellosis. Materials and Methods: Our study was conducted on 271 volunteers engaged in livestock farming in 20 districts of Erzurum province between 2020 and 2021. Brucella antibodies were investigated in blood samples using ELISA IgG, ELISA IgM, Rose Bengal, and Standard tube agglutination tests. A questionnaire was administered to the participants to investigate the risk factors of brucellosis. Results: The mean age of the participants was 43.6 ± 15.7.2 years (min:18, max:90), and there were 137 male (50.6%) and 134 female (49.4%) particpants. Seropositivity was detected with ELISA IgG in 40 of 271 participants (14.8%). Seropositivity was detected in the ELISA IgM test in 2 of these 40 participants (0.7%). Seropositivity was found in 46 participants (17%) in the Rose Bengal and 29 individuals in the STA test. According to the serology results, ELISA IgG positivity was higher in male participants compared to female participants (ratio=1.6). Among pet owners, ELISA IgG seropositivity was found higher than the participants who did not have pets (ratio=1.9). In the evaluation based on educational status, the rate of seropositivity was slightly higher in the participants who were illiterate and had a poor level of education. Conclusion: In our study, it was determined that the prevalence rate obtained by ELISA IgG was consistent with previous studies conducted in the region. No significant relationship was observed between the serology results of the participants and their gender and educational status. On the other hand, the positivity of ELISA IgG results was higher among the participants who had pets, and there was a significant relationship at the margin.